Impact of calcification on percutaneous coronary intervention: MACE‐Trial 1‐year results - Sharma, Samin K.; Bolduan, Ryan W.; Patel, Manesh R.; Martinsen, Brad J.; Azemi, Talhat; Giugliano, Gregory; Resar, Jon R.; Mehran, Roxana; Cohen, David J.; Popma, Jeffrey J.; Waksman, Ron (Catheterization and cardiovascular interventions, 2019)
Objectives The Multi‐center Prospective Study to Evaluate Outcomes of Moderate to Severely Calcified Coronary Lesions (MACE—Trial) was designed to provide further insight on the impact of calcification on procedural and long‐term percutaneous coronary intervention outcomes. Background Prior studies evaluating the impact of lesion calcification on percutaneous coronary intervention outcomes are limited by: retrospective nature, pooled data from multiple studies, or lack of specificity around calcification with only operator assessment and without core lab evaluation. Methods The MACE‐Trial was a prospective, multicenter, observational clinical study that enrolled 350 subjects at 33 sites from September 2013 to September 2015. Core lab assessed subject stratification by lesion calcification (none/mild [N = 133], moderate [N = 99], and severe [N = 114]). Endpoints were lesion success, procedural success, and 1‐year major adverse cardiac events (MACEs). Results Presence of severe calcification had significant impact on lesion success ([83.3%] versus none/mild calcification [94.7%, P = 0.006]) and procedural success ([86.8%] versus moderate [95.0%, P = 0.028], and none/mild [97.7%, P = 0.001]). 1‐year MACE rates were associated with presence of calcification in subjects with none/mild (4.7%), moderate (8.7%), and severe (24.4%) (P < 0.001) calcification; however, no difference was noted between none/mild and moderate (P = 0.237). The risk adjusted multivariable model identified severe calcification and decreasing eGFR as predictors of 30‐day and 1‐year MACE. Conclusions In this prospective study, patients with severe calcification had significantly worse outcomes compared to those without; however, unlike previous retrospective studies, moderate calcium resulted in similar outcomes as none/mild calcium. Clinical Trial Registration URL: https://clinicaltrials.gov/ct2/show/NCT01930214. Unique Identifier: NCT01930214.